Características das emissões na faixa do extremo ultravioleta (EUV) durante uma explosão solar classe X8.2 ocorrida no limbo solar - Santos, Tallyta Layanne de Almeida (2021)
Flares are defined observationally as a sudden enhancement of emission in different wavelengths of the electromagnetic spectrum. In this work we investigate the characteristics of EUV emission associated with a X8.2 class flare that occurred near to the solar limb on September 10, 2017. This event appears in the HEK database with onset at 15:35:00 UT and emission peak at 16:06:00 UT. It is associated to active region NOAA 12673, which was initially classified as alpha-type according to the Mt. Wilson classification rules of magnetic complexity. When this active region crossed the center of the solar disc, its magnetic complexity changed to beta-gamma.Images on the continuum show that the region was associated with a group of irregular sunspots, and magnetic field measurements indicate that the region is formed by interacting positive and negative polarities, giving rise to more than one polarity inversion line. The image analysis in the EUV wavelength range for a period that starts at 13:00:00 UT and ends at 19:00:00 UT, indicates that the plasma is confined by a complex magnetic field that connects different solar surface regions and evolves almost statically until the moment of flare. After that, the magnetic field starts to evolve dynamically, forming a post-flare loop structure. In the EUV images it is also possible to identify the occurrence of a plasma jet preceding the event and, in the 94 e 131Å images, it is observed a filament structure that could be associated with a current sheet. The light curves obtained from the images show, at first, an emission enhancement at about 15:45:00 UT due to the plasma jet, followed by a sudden increase in the emission with the first peak occurring at about 16:07:00 UT. The wavelet analysis of the light curve indicates the appearance of short-period oscillations, which suggests that superimposed on an emission continuum source exists a pulsed component that acts from the appearance of the jet until the onset of the EUV emission decay phase. The temporal evolution of the mean vertical emission profile shows that emission sources appear first in the lower atmosphere and, as time goes by, they move to higher solar atmosphere regions, reaching at the end distances of about 42 Mm from the solar surface. It is also observed that the displacement velocity of the source slows down over time. Finally, we also applied a descriptive statistical analysis to the data through the calculation of the central tendency and dispersion metrics. Before the occurrence of the flare, the pixels in each image show a distribution of values close to the normal distribution, with the mean and median values close to each other. From the instant that the emission enhancement associated with the flare occurs, the mean and median values separate from each other. The mean increases way above the median values, indicating that the distribution starts to present a right tail. The dispersion metrics are also changed with the event onset, with the standard deviation and the difference between the largest and the smallest value showing more significant changes than the mean median deviation and the interquartile range. Two measures that present sensitivity to the appearance of outliers are the skewness and kurtosis, both present an enhancement during the eruption.